Predicting Factors Influencing Purchase of Aashirvaad Brand Using Logistic Regression - Ramaiyan, Arunmozhi (Indian Journal of Marketing, 2011)
Consumers purchase preference is dynamic because the thinking, feeling and actions of individual consumers is constantly changing. Consumers belonging to different age groups, gender, occupations and monthly incomes will differ in their opinion towards the products launched by corporates. The assumption here is that people having common demographic characteristics behave in an identical manner and will have same preferences. Demographic characteristics have also served as the basis for segmenting the market. In India, consumers today see an exciting explosion of choices like new product categories, new brands, new shopping options and have an increasing disposable income to fulfill their aspirations. Consumers are seeking more information to make these choices. A key challenge for consumers is to identify the multiple brands which are crowding on the shopping stores.